2016
DOI: 10.18632/oncotarget.12659
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant ceRNA-mediated regulation of KNG1 contributes to glioblastoma-induced angiogenesis

Abstract: Glioblastoma is a highly vascularized brain tumor that causes high mortality. Kininogen-1 (KNG1) has demonstrated both tumor suppressor and antiangiogenesis properties in gliobastoma cells. We analyzed the microarray and proteomic profiles of tumor tissues from glioblastoma patients (N = 180), and identified potential RNA regulators of the KNG1. Validation experiments in U87 glioblastoma cells showed that the regulation of KNG1 by CTU1, KIAA1274, and RAX was mediated by miR-138. The siRNA-mediated knockdown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Bradykinin plays an important role in several physiological activities such as antimicrobial, smooth muscle contraction and release of inflammatory mediators like prostaglandins (65). Moreover, bradykinin is also known to interact with EGFR and stimulate downstream signaling pathways to enhance cell invasion as well as promote angiogenesis through elevated VEGF expression in glioma (66,67). Furthermore, higher expression of kininogen 1 is recently reported as a serum biomarker of advanced colorectal adenoma, colorectal cancer and prognostic marker of oral cancer (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin plays an important role in several physiological activities such as antimicrobial, smooth muscle contraction and release of inflammatory mediators like prostaglandins (65). Moreover, bradykinin is also known to interact with EGFR and stimulate downstream signaling pathways to enhance cell invasion as well as promote angiogenesis through elevated VEGF expression in glioma (66,67). Furthermore, higher expression of kininogen 1 is recently reported as a serum biomarker of advanced colorectal adenoma, colorectal cancer and prognostic marker of oral cancer (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some immune-related lncRNAs such as RP11-161H23.5 contributes to the prognosis prediction of GBM via certain lncRNA-miRNA interactions [46]. Actually, the lncRNA-miRNA-mRNA regulation take part in the malignant progression of GBM disease identi cation and functional characterization [47]. A previous differential correlation analysis of GBM reveals that immune ceRNA interactions can be used to predict the patient survival [48].…”
Section: Discussionmentioning
confidence: 99%
“…We have found that some genes have not been thoroughly studied in zebrafish, but have been identified to be important in human brain neural networks and diseases. For example, kng1 (kininogen 1) demonstrated tumor suppression and anti-angiogenic properties in glioblastoma [30]. Aldh1l1 (aldehyde dehydrogenase 1 family member L1) was also identified as a new astrocyte-specific marker in the brain [31].…”
Section: Discussionmentioning
confidence: 99%